Mariner‐based transposon mutagenesis for Bacteroides species. (20th May 2013) - Ichimura, Minoru; Uchida, Keiko; Nakayama‐Imaohji, Haruyuki; Hirakawa, Hideki; Tada, Tomoyo; Morita, Hidetoshi; Yasutomo, Koji; Okazaki, Katsuichiro; Kuwahara, Tomomi
Abstract Bacteroides is one of the most predominant groups of human gut microbiota. Recent metagenomic analyses and studies on gnotobiotic mice demonstrated the tight association of Bacteroides with epithelial function, the gut immune system and systemic metabolism in the host. The mariner family transposon shows relatively low target site specificity and has hosts ranging from prokaryotes to eukaryotes. Thereby, random mutagenesis using the mariner family transposon is expected to identify key molecules for human‐Bacteroides symbiosis. In this study, we constructed the plasmid pMI07 to deliver the gene cassette (ermF/ITR), which harbors the erythromycin resistant marker (ermF) and the inverted repeat sequences (ITRs) recognized by Himar1 transposase, to Bacteroides via electrotransformation. pMI07 successfully delivered ermF/ITR to the Bacteroides genomes and generated thousands of insertion mutants/μg of pMI07 in B. thetaiotaomicron, B. fragilis, B. ovatus, and also, although to a lesser extent, B. vulgatus. Analyses of the ermF/ITR insertion sites in B. thetaiotaomicron and B. vulgatus revealed that the cassette targeted the dinucleotide TA and integrated into the genomes in an unbiased manner. The data reported here will provide useful information for transposon mutagenesis in Bacteroides species, which will enable identification of the genes responsible for their unique phenotypes.